Problematika Pembacaan Keterangan Saksi oleh Penyidik dalam Perspektif Hukum Acara Mahkamah Agung - Edward, Ryan Fransisco; Wiraguna, Sidi Ahyar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Constitutional Court (Mahkamah Konstitusi/MK), as the guardian of the Constitution, plays a vital role in upholding the rule of law and protecting citizens' constitutional rights. One crucial aspect of judicial proceedings is the evidentiary process through witness testimony. However, the practice of reading out the official investigation report (Berita Acara Pemeriksaan/BAP) by investigators without the physical presence of witnesses in court raises legal issues, particularly regarding the principles of audi et alteram partem and due process of law. This study aims to examine the validity and legal implications of witness statements being read by investigators from a Constitutional Court procedural law perspective. The research adopts a normative and empirical juridical approach, analyzed through descriptive qualitative methods. The findings reveal that reading witness statements without their direct presence in court weakens evidentiary value and generates legal uncertainty. Although the Constitutional Court, through Decision No. 65/PUU-VIII/2010, expanded the definition of a witness, it did not eliminate the importance of direct examination in court. Compared to common law and continental legal systems, Indonesia’s legal system still requires reform to ensure the protection of defendants' rights. Therefore, clear legal standards and technical guidelines are needed to balance effective law enforcement with the protection of human rights.